The Estrela Geopark: from Planation Surfaces to Glacial Erosion - Vieira, Gonçalo (2021)
The Estrela Geopark rises to 1993 m asl and occupies an area over 2000 km2 in the western sector of the Iberian Central System, the mountain range that extends from Guadarrama in Spain to Montejunto in the north-west of Lisbon. The Estrela is located in the Central Iberian Zone showing various types of granites and the turbiditic metasediments of the Beiras Group as the main lithologies. After the planation of the Variscan orogen, the Alpine compression uplifted the Iberian Central System and rejuvenated the landscape, elevating the planation surfaces in a pop-up structure and accelerating fluvial erosion along the main Late Variscan faults. The elevation of the Serra da Estrela, the plateau character of the summit and its position as the first barrier to the moist Atlantic air masses entering Iberia, generated the ideal conditions for fast glacial inception during the cold phases of the Pleistocene. The last glacial showed the formation of an extensive plateau ice field and several valley glaciers, which deeply sculpted the landscape, leaving an excellent imprint of glacial processes in the mountain. The interplay of glacial erosion, granite weathering, tectonics and fluvial erosion generated a landscape of very high scenic, scientific and educational value. These, together with a rich biodiversity and long history of human presence with strong cultural and economic links to the mountain, are the main reasons for the labelling of the Estrela as a UNESCO Global Geopark.